2020
DOI: 10.3390/pharmacy8010045
|View full text |Cite
|
Sign up to set email alerts
|

Substandard and Falsified Medicines in Myanmar

Abstract: Background: substandard and falsified medicines (SFMs) are a threat to public health. The availability of SFMs in Myanmar was reported by the World Health Organization (WHO) in 1999, but there have been few systematic surveys on falsified medicines in Myanmar since then. The aim of this study is to examine the extent of SFMs for sale in Myanmar. Methods: target medicines were tablets of candesartan, metformin, and pioglitazone, and infusions of ciprofloxacin and levofloxacin. Samples were collected from hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
1
13
1
Order By: Relevance
“…Four recent studies by Kimura and coworkers reported that authenticity responses were received from the manufacturers for 0%, 8.7%, 9.5%, and 28.8% of the investigated samples, respectively. 40 43 In comparison, the response rate of 49.5% obtained in the present study is reasonably high, despite interference by the COVID-19 pandemic. Higher response rates were reported from two earlier studies of the Kimura group.…”
Section: Discussionsupporting
confidence: 65%
“…Four recent studies by Kimura and coworkers reported that authenticity responses were received from the manufacturers for 0%, 8.7%, 9.5%, and 28.8% of the investigated samples, respectively. 40 43 In comparison, the response rate of 49.5% obtained in the present study is reasonably high, despite interference by the COVID-19 pandemic. Higher response rates were reported from two earlier studies of the Kimura group.…”
Section: Discussionsupporting
confidence: 65%
“…It is sold in the market as a single product under the brand name Actos or in combination with metformin (Actoplus Met, Actoplus Met XR) and glimepiride (Duetact) [19,20]. A few reports on the quality of pioglitazone and other medicines from China or Myanmar have appeared [21][22][23], and provide useful data for comparison with the findings of this study. Additionally, recent reports on the nitrosamine impurities detected in ranitidine and pioglitazone products suggest the presence of scarce quality pioglitazone products in the market [24,25].…”
Section: Introductionmentioning
confidence: 89%
“…The production and distribution of substandard and falsified medicines (SFs) are increasing throughout the world 1 3 . Lower and middle-income countries (LMICs) are most affected, but developed countries are not immune 4 – 6 .…”
Section: Introductionmentioning
confidence: 99%